Brain-derived neurotrophic factor Val66Met and blood glucose: a synergistic effect on memory - Raz, Naftali; Dahle, Cheryl L.; Rodrigue, Karen M.; Kennedy, Kristen M.; Land, Susan J.; Jacobs, Bradley S. (Frontiers in Human Neuroscience, 2008)
Age-related declines in episodic memory performance are frequently reported, but their mechanisms remain poorly understood. Although several genetic variants and vascular risk factors have been linked to mnemonic performance in general and age differences therein, it is unknown whether and how they modify age-related memory declines. To address that question, we investigated the effect of Brain-Derived Neurotrophic Factor (BDNF) Val66Met polymorphism that affects secretion of BDNF, and fasting blood glucose level (a vascular risk factor) on episodic memory in a sample of healthy volunteers (age 19-77). We found that advanced age and high-normal blood glucose levels were associated with reduced recognition memory for name-face associations and poorer prose recall. However, elevated blood glucose predicted lower memory scores only in carriers of the BDNF 66Met allele. The effect on associative memory was stronger than on free recall. These findings indicate that even low-level vascular risk can produce negative cognitive effects in genetically susceptible individuals. Alleviation of treatable vascular risks in such persons may have a positive effect on age-related cognitive declines.